China And The Knowledge Economy : Challenges And Opportunities - Zeng, Douglas Zhihua (The World Bank, 2007)
The rapid pace of economic growth in China has been unprecedented since the start of economic reforms in late 1970s. It has delivered higher incomes and made the largest single contribution to global poverty reduction. Measured by international poverty lines, from 1978-2004, the absolute poor population in rural areas has dropped from 250 million to 26.1 million. Such gains are impressive and have been driven largely by a set of market-oriented institutional reforms, strong investment, and effective adoption and application of various knowledge and technologies, especially foreign ones through trade and foreign direct investment. While enjoying tremendous success, China also faces many challenges that need to be addressed to sustain its long-term development. These include weak institutions, low overall educational attainment, weak indigenous innovation capacity, poor links between research and development and industries, and so on. This paper provides an analysis of some strengths, weaknesses, opportunities, and challenges to China's knowledge economy in the areas of economic incentives and institutional regime, human capital, innovation system, and information infrastructure